A new book on the history of the Murman coast colonization - Dmitry A. Gerasimov (Arctic and North, 2018)
The review of the book by P.V. Fedorov and A.A. Malashenkov “Soil on the Northern rocks: Orthodox necropolis of the Murmansk coast of the Barents Sea (1863–1920)”. The study based on the processing of metrical books made it possible to publish the information about 2,524 persons of the Orthodox religion buried on the Murmansk coast, or drowned in the sea in 1863–1920. The Authors found the demographic statistics related to the appearance of the settlements with permanent population. The book clarifies the idea of “cultural soil”, local and family-genealogical structures in the Russian Arctic, and it also contributes to the historical personification of the Murmansk coast.